Growth and productivity of a young apple orchard at different spacing - Csigai, K.; Hrotkó, K. (International Journal of Horticultural Science, 2005)
Planting of new high density apple orchards showed an increasing tendency over the last ten years. Growers use in those orchards mainly dwarfing or semi dwarfing rootstocks. The spacing for those orchards is recommended based on Dutch and German experiences; however, the optimization of orchard planting density as a key factor for successful orchard management should consider the local climate conditions. An experimental orchard was planted in 2000 to investigate the effect of spacing on three dwarfing rootstocks with two apple cultivars `Jonica’ and ’Gala Must’. We compared 8 planting densities (1270-3704 tree/ha) and two tree shapes (slender spindle and vertical axis). In this paper the data of the first five years’ growth and bearing are presented. After 4 years, the decreasing tree densities caused reduced trunk cross sectional area. Tree density had a significant positive effect on cumulative yield per hectare. From the examined rootstocks, M.9 Burgmer 984 gave the smallest canopy for both cultivars. The trees on M.9 T.337 and on Jork 9 rootstocks have stronger growth. The light interception was measured under the canopy by AccuPAR (Decagon Devices Inc.’s).